The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1071/rd16528
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP19A1 gene polymorphisms with anoestrus in water buffaloes

Abstract: Cytochrome P450 aromatase (encoded by the CYP19A1 gene) regulates oestrogen biosynthesis and so plays an essential role in female fertility. We investigated the genetic association of CYP19A1 with the risk of anoestrus in Egyptian water buffaloes. A total of 651 animals (326 anoestrous and 325 cycling) were used in this case-control study. Using single-strand conformation polymorphisms and sequencing, four single nucleotide polymorphisms (SNPs) were detected; c.-135T>C SNP in the 5'UTR and three non-synonymous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…This study is part of a broader project targeting the genetic improvement of the of Egyptian water buffaloes. We previously screened IGF1, IGF1R, IGF2, IGF2R, and Cyp19A1 for polymorphisms and analyzed their associations with growth traits and fertility [15,16,18,24,26]. Herein, we extended our investigation to identify genetic variations in the GHR gene and determine their potential effects on milk production traits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a broader project targeting the genetic improvement of the of Egyptian water buffaloes. We previously screened IGF1, IGF1R, IGF2, IGF2R, and Cyp19A1 for polymorphisms and analyzed their associations with growth traits and fertility [15,16,18,24,26]. Herein, we extended our investigation to identify genetic variations in the GHR gene and determine their potential effects on milk production traits.…”
Section: Resultsmentioning
confidence: 99%
“…Again, Shi et al [13] did not study the effect of this important SNP on milk production and milk quality traits in buffaloes. Although many studies reported the ability of noncoding polymorphisms including: synonymous, intergenic and intronic SNPs to modify complex traits in animals [14][15][16], it is still essential to study non-synonymous SNPs, as they could directly alter the amino acids sequence, which could possibly lead to phenotypic variation. Therefore, in this study, we screened coding sequences of E4-E6 and E8 for polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…About 1 g of kidney and liver of each euthanized animal were separated, perfuse with phosphate buffer saline solution (PBS) solution (pH, 7.4) containing 0.16 mg/ ml heparin to remove any blood or clots, and homogenized in 9 ml PBS solution using tissue homogenizer (Glas-Col. Tissues homogenizer, China). Homogenate aliquots were centrifuged at 10,000 × g for 30 min, supernatant were removed and stored at -80 till the time of assessment of concentration of malondialdehyde (MDA) and activity of glutathione peroxidase enzymes (GPX) using locally available kits (BiodiagnosticEgypt; Biovision, USA) and as previously described (35). Protein content was detected using Bradford's reagent (Sigma-Aldrich, USA).…”
Section: Antioxidant Studiesmentioning
confidence: 99%
“…The luteinising hormone beta polypeptide ( LHB ) (Cheng et al ) and gonadotropin‐releasing hormone receptor ( GnRHR ) (Wang et al ) were recently shown to be associated with semen production traits, including ejaculate volume and sperm qualities, in Chinese swamp buffaloes. Variants affecting Egyptian river buffalo female fertility, in terms of susceptibility to anoestrus, have been identified at four SNPs, one in the 5′UTR and three in exon 10 of the cytochrome P450 aromatase ( CYP19A1 ) gene (El‐Bayomi et al ). Similarly, pregnancy rate seems to be associated with different genotypes at the melatonin receptor 1A ( MTNR1A ) gene in melatonin‐treated Murrah river buffaloes (Pandey et al ).…”
Section: Introductionmentioning
confidence: 99%